STRATEGIC EFFICIENCY OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN HEALTHCARE MANAGEMENT (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This research paper examines the role and impact of Artificial Intelligence (AI) systems on the management and operational efficiency of modern healthcare institutions. The study analyzes the integration of AI algorithms in diagnostic accuracy, administrative cost optimization, and patient flow management. The primary objective is to provide a scientific basis for healthcare managers regarding the economic and social advantages of technological transformation. The findings suggest that AI-driven management models can drastically reduce hospital overheads while enhancing patient care quality.
Keywords: Artificial Intelligence (AI), Healthcare Management, Machine Learning, Health Economics, Digital Transformation, Big Data, Predictive Analytics, Smart Hospital.